Upaya Pencegahan HIV/AIDS dalam Meningkatkan Derajat Kesehatan Masyarakat Dengan Pendidikan Kesehatan di SMAN 1 Parongpong - Theophylia Melisa Manumara; Setia Yoga Bayu Aditia; Gilba Fatina Andrian; Natasya Bilbina; Siti Hasna Nafilah; Hana Sri Oktaviani; Yunita Siti Wahyuni; Devi Siti Masitoh; Mila Laelatul Hasanah; Sahrun Sahrun; Rifalza Dwi Yanti (Jurnal Medika: Medika, 2026)
HIV/AIDS remains one of the public health issues that continues to rise in Indonesia, including in West Java Province. Adolescents’ limited knowledge of HIV/AIDS can increase the risk of engaging in risky behaviors and foster negative stigma toward people living with HIV/AIDS. This health education activity aims to improve students’ knowledge regarding HIV/AIDS prevention efforts through leaflets at SMAN 1 Parongpong. The method used was a quasi-experimental design with a pretest-posttest approach involving 29 eleventh-grade students selected using purposive sampling. The activity was conducted through the administration of a pretest, presentation of materials using PowerPoint and leaflets, interactive discussion, and a posttest. The instrument used was a questionnaire containing 20 questions regarding the definition, modes of transmission, risky behaviors, and prevention HIV/AIDS. The results of the activity showed that health education using leaflets was able to increase students’ knowledge and understanding of HIV/AIDS. In addition, students appeared active and enthusiastic during the educational process. Thus, health education using leaflets is effective as a promotive and preventive measure in raising awareness among adolescents regarding HIV/AIDS prevention.